ChemInform Abstract: Novel Structures and Physics of Nanomagnets (Invited). Issue 26 (June 2015) - Sellmyer, D. J.; Balamurugan, B.; Das, B.; Mukherjee, P.; Skomski, R.; Hadjipanayis, G. C.
Abstract Review: 50 refs.